The safest point method as an efficient tool for reliability-based design optimization applied to free vibrated composite structures - Ghias Kharmanda (Advanced Engineering Research)
Introduction. Reliability-Based Design Optimization (RBDO) model reduces the structural weight in uncritical regions; it provides not only an improved design but also a higher level of confidence in the design. Materials and Methods. The classical RBDO approach can be carried out in two separate spaces: the physical space and the normalized space. Since lots of repeated researches are needed in the above two spaces, the computational time for such an optimization is a big problem. Fortunately, an efficient method called the Hybrid Method (HM) has been elaborated by which the optimization process is carried out in a Hybrid Design Space (HDS). When designing free vibrated structures, the HM can be used with a big implementation complexity, and that leads to high computing time. An efficient method called Safest Point (SP) method is developed to overcome this drawback. Research Results. A numerical application on the composite aircraft wing under free vibrations shows the efficiency of the proposed method relative to the HM. The SP method can reduce efficiently the computing time relative to the HM. Discussion and Conclusions. The simplified implementation framework of the SP strategy consists of decoupling the RBDO problem into a number of simple problems. That provides designers with efficient solutions that should be economically justified for a required reliability level for dynamic cases (modal studies).